Targeted epigenetic repression of a lymphoma oncogene by sequence-specific histone modifiers induces apoptosis in DLBCL. Issue 2 (1st February 2017) - Luo, Hong; Schmidt, Jennifer A.; Lee, Yi-Shan; Oltz, Eugene M.; Payton, Jacqueline E.
Abstract: Alterations to the epigenetic landscape of diffuse large B-cell lymphoma (DLBCL) play a fundamental role in deregulating genes involved in normal lymphocyte differentiation. To determine whether targeted epigenetic therapy could reverse these pathogenic chromatin changes and suppress the expression of a lymphoma oncogene, we focused on BCL6, a transcriptional repressor whose aberrant expression is tightly linked to DLBCL proliferation and survival. We fused zinc-finger (ZF) domains specific for regulatory regions in the BCL6 locus to a repressive epigenetic modifier, the Kruppel-associated box (KRAB) repressor domain. Distinct ZF–KRAB fusions repressed the local chromatin landscape, suppressed BCL6 expression, significantly impaired DLBCL growth, and caused widespread cell death in a BCL6 -dependent manner. Importantly, expression of ectopic BCL6 protein rescued ZF–KRAB-induced cell death, demonstrating the modifiers' specificity. We show that sequence-specific epigenetic modifiers can alter oncogene expression and induce apoptosis in cancer cells, underscoring their potential for future development as targeted epigenetic protein therapies.